Visual aesthetic of Petta Puang theater group performance in South Sulawesi - Mukadas, Andi Baetal; Florentinus, Totok Sumaryanto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This study aims to provide a description of the visual aesthetics contained in the show Puppet Theater Petta Puang in South Sulawesi in connection with the network of symbolic meaning inherent in it. The method used is descriptive-interpretivime method symbolic, with data collection techniques through direct observation, interviews, and documentation. The result of the research shows that in the performance of Petta Puang Puppet Theater there is a visual aesthetic that characterizes the main character «Petta Puang» in every appearance that is jas tutup, songkok guru (songkok to Bone), and lipa ‘sabbe’. Some visual aesthetics have symbolic meaning directly related to the socio-cultural values of the people of South Sulawesi. Lipa ‘sabbe (silk sarong) is a Bugis sarong which has a fine texture as a representation of the tenderness and social politeness of Bugis tribe, while vertical and horizontal lines are markers of human relationship with God and human relationships in the social system. Jas Tutup originally consists of two colors, namely black and white. Two elements of color is a neutral color that confirms the impression of depth and sanctity that became the patron of Bugis tribe values.